Rancang Bangun Test Bench Electric Starting Motor - Abdul Halim; Mangkona Mangkona; Said Fahmi; Alimuddin Alimuddin; Adriansyah Adriansyah (MEDIA PERSPEKTIF : Journal of Technology, 2021)
The progress and development of the industrial world in this industrial era requires technicians to improve their abilities to understand and understand how a system works and how the process of doing work according to procedures, one of the absolute requirements that must be owned by all human resources working in the industrial sector. heavy equipment. The Test Bench is a tool that makes it easy to carry out the disassembly and assembly of electrical components in a portable way. The design of the Test Bench is the main support in making the tool so that it can be used for testing tools. There are several stages in the process of making the Test Bench including the selection of materials, tools, the process of cutting materials, the process of drilling materials, the process of welding, and the process of painting. The Test Bench for starting the motor makes it easier for practical work on disassembly, assembly and testing of starting motors to be more efficient, effective and timely based on the procedures that have been made.